Načrtovanje in karakterizacija peptidnih ligandov za vezavo regije Fc imunoglobulinov - Bozovičar, Krištof (visokošolska dela, 2021)
Monoclonal antibodies (mAbs) of IgG isotype are widely used as therapeutics for treatments for cancer, autoimmune and chronic inflammatory, infectious, and many other diseases. They also make invaluable biorecognition agents due to remarkable specificity and affinity towards diverse antigens. Affinity chromatography based on bacterial immunoglobulin-binding proteins (i.e., staphylococcal protein A (spA) or streptococcal protein G (spG)) represents the cornerstone of antibody isolation and purification. Such protein affinity ligands suffer from ligand instability and leaching. Peptides represent a viable alternative to complex protein ligands. As affinity ligands, they bind target proteins with high specificity, but moderate affinity, thus requiring mild elution conditions. They are also small and simple, and thus available through cost-efficient chemical synthesis with consistent quality even on a large scale. Furthermore, the potential leaching of peptides from affinity matrices is not a major issue regarding the augmented product immunogenicity. We have previously identified a peptide ligand (min19FC-Q6D; GSYWYDVWF) that binds to human IgGs. We designed a focused phage display peptide library based on randomization of selected non-essential residues of the parent peptide. Non-essential residues were either fully or partially randomized to produce a library of 64000 peptide members. Phagemid pIT2 was modified to remove the encoded long peptide linker anchoring the displayed peptide to the p3 phage coat protein, as we have observed that long flexible linkers negatively influence binding. We have subcloned the library insert into the modified pIT2-SL phagemid and generated the phage library. A single selection round was performed using a stepwise elution with buffers of progressively descending pH values. The initial library (before the panning session) and eluted fractions were subjected to deep sequencing to identify highly enriched clones. These were then tested for affinity in phage display ELISA assay. Peptide A (GSYWYNVWF) exhibited the highest affinity compared to other enriched binders and the parent peptide. Peptide A was used to construct several affinity matrices with linker molecules of different length and rigidity. The most effective resin for antibody capture utilized the brached linker tris(2-aminoethyl)amine. We suspect that the high capture capacity was due to the increased ligand density (compared to other linker molecules)/avidity effects and forced ligand orientation towards the solute. The goal of this doctoral thesis was the construction of an affinity column for IgG capture. The column constructed with the selected branched linker and peptide A demonstrated a dynamic binding capacity (~43 mg IgG1 /mL resin) and specificity on par with commercially employed protein A-based resin, but with higher stability (i.e., resistance to 0,5 M NaOH). We have attempted to obtain peptide:Fc region interaction information via X-ray crystallography. Fc fragment was obtained by papain digestion of monoclonal IgG1 and co-crystallized with the parent peptide min19Fc-Q6D. Several crystals were obtained under various conditions. Using the high-resolution diffraction data (resolution approx. 2,2 A; collected at Elettra Sincrotrone Trieste) we solved the structure employing phasing by molecular replacement. However, there was electron density scattering in one of the CH2 region, and no bound peptide was observed. We assume that the lack of defined electron density in the CH2 domain region indicates a conformational change of a fraction of Fc molecules in the crystal, triggered by interaction with the peptide.
Keywords: afinitetna kromatografija; disertacije; Imunoglobulini; imunoglobulini IgG; Laboratorijska kemija; monoklonska protitelesa; peptidni ligandi; predstavitev na bakteriofagu; usmerjena knjižnica